SIRT7-mediated NRF2 deacetylation promotes antioxidant response and protects against chemodrug-induced liver injury - Tingzi Yu; Cong Ding; Jinying Peng; Gaoshuang Liang; Yongyi Tang; Jinqiu Zhao; Zhuan Li (Cell Death and Disease)
Abstract NRF2 has been recognized as a central hub that neutralizes ROS and restores intracellular redox balance. In addition to KEAP1 mediated ubiquitin-proteasome degradation, post-translational modifications of NRF2 are critical for regulating its nuclear translocation and activation but precise mechanisms underly this regulation remain elusive. In this study, we found that SIRT7 was sufficient and essential for NRF2 nuclear localization and activation. Knockdown of SIRT7 significantly impaired intercellular ROS homeostasis and increased apoptosis in response to oxidative stress including chemodrug treatment. SIRT7 interacted with NRF2 and induced its deacetylation, by which inhibited binding of NRF2 to KEAP1, enhanced NRF2 protein stability and promoted its nuclear translocation. SIRT7 induced NRF2 deacetylation at K443 and K518 sites. Lysine-arginine mutations of these sites (2KR NRF2) significantly reduced KEAP1/NRF2 binding, increased NRF2 nuclear translocation and target gene expression, decreased intercellular ROS level, whereas lysine-glutamine (2KQ) mutant showed similar subcellular localization and functions with WT. Knockdown SIRT7 in hepatocyte exacerbated Oxaliplatin (Oxa) induced hepatic injury and inflammation. While AAV8-NRF2-mediated hepatic NRF2 overexpression or NRF2 agonist significantly prevented Oxa-induced elevation of ALT levels, sinusoidal dilatation and inflammation in SIRT7 HKO mice. Our data thus uncovered previously unidentified role of SIRT7 in modulating NRF2 nuclear localization and activation via deacetylation. Activating SIRT7 might offer protection against chemodrug-induced liver injury.